1985
DOI: 10.1002/1097-0142(19850501)55:9<1973::aid-cncr2820550924>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and pathologic complications associated with peritoneovenous shunts in management of malignant ascites

Abstract: Forty‐three peritoneovenous shunts have been inserted to palliate malignant ascites in 33 patients. Ascites was controlled for a time in every patient, but 18 shunts eventually blocked. Further shunt revision successfully controlled ascites until death in five of these patients and for prolonged periods in another five. The authors observed a marked difference between the performances of the two available shunts, but emphasize that the two groups of patients were not selected at random and therefore may not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…None of the qRT-PCR assays address the question of the biological relevance of detecting tumour cells in blood or LN and do not provide any information about their metastatic potential or take into account the role of patient genotype in allowing or suppressing metastasis. Animal models suggest that only 0.01 % of cells circulating in the blood ultimately develop into a metastatic site [137], and in humans the likelihood of tumour cells seeding to become metastases is also very low [138]. Furthermore, the genotype of LN metastases differs from that of the main clone in the primary tumour in > 50 % of patients, with a significant minority displaying a genotype not detected in the primary tumour at all [138].…”
Section: Disease-associated Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the qRT-PCR assays address the question of the biological relevance of detecting tumour cells in blood or LN and do not provide any information about their metastatic potential or take into account the role of patient genotype in allowing or suppressing metastasis. Animal models suggest that only 0.01 % of cells circulating in the blood ultimately develop into a metastatic site [137], and in humans the likelihood of tumour cells seeding to become metastases is also very low [138]. Furthermore, the genotype of LN metastases differs from that of the main clone in the primary tumour in > 50 % of patients, with a significant minority displaying a genotype not detected in the primary tumour at all [138].…”
Section: Disease-associated Detectionmentioning
confidence: 99%
“…Animal models suggest that only 0.01 % of cells circulating in the blood ultimately develop into a metastatic site [137], and in humans the likelihood of tumour cells seeding to become metastases is also very low [138]. Furthermore, the genotype of LN metastases differs from that of the main clone in the primary tumour in > 50 % of patients, with a significant minority displaying a genotype not detected in the primary tumour at all [138]. In addition, humans themselves are genetically polymorphic, and the outcome of metastasis depends on the interplay of tumour cells with various host factors, including the organ microenvironment, which can influence the biology of cancer growth, angiogenesis and metastasis [139].…”
Section: Disease-associated Detectionmentioning
confidence: 99%
“…A recent microarray analysis of the expression signature of solid cancers suggests that the metastatic potential of human tumours is encoded in the bulk of a primary tumour (Ramaswamy et al, 2003). Animal models suggest that only 0.01% of cells circulating in the blood ultimately develop into a metastatic site (Fidler, 1990a) and in humans the likelihood of tumour cells seeding to become metastases is also very low (Souter et al, 1985). Furthermore, the genotype of LN metastases differs from that of the main clone in the primary tumour in >50% of patients, with a significant minority displaying a genotype not detected in the primary tumour at all (Souter et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models suggest that only 0.01% of cells circulating in the blood ultimately develop into a metastatic site (Fidler, 1990a) and in humans the likelihood of tumour cells seeding to become metastases is also very low (Souter et al, 1985). Furthermore, the genotype of LN metastases differs from that of the main clone in the primary tumour in >50% of patients, with a significant minority displaying a genotype not detected in the primary tumour at all (Souter et al, 1985). In addition, humans themselves are genetically polymorphic, and the outcome of metastasis depends on the interplay of tumour cells with various host factors including the organ microenvironment which can influence the biology of cancer growth, angiogenesis, and metastasis (Fidler, 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…However, the fluid usually reaccumulates rapidly, and aspirations provide only temporary relief. The use of peritoneovenous shunting for malignant ascites has been widely described.4,6,8-' 1~' [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Malignant ascites has also been treated by intraperitoneal instillation of radioactive colloids A u '~~ P32) or chemotherapeutic agents (tetracycline, bleomycin, Adriamycin [Adria Laboratories, Columbus, OH], Nitrogen mustard, or cisplatin). Although it has been reported that these modalities yield response rates of 35% to 4070,~ they have most often been used as alternatives to peritoneovenous shunting.…”
mentioning
confidence: 99%